Ancient Christian commentary on Scripture. Old Testament - Oden, Thomas C. (Downers Grove, IL : InterVarsity Press, 2001)
"The Ancient Christian Commentary on Scripture does what very few of today's students of the Bible could do for themselves. With the aid of computer technology, the vast array of writings from the church fathers - including much that is available only in the ancient languages - have been combed for their comment on Scripture. From these results, scholars with a deep knowledge of the fathers and a heart for the church have hand-selected material for each volume, shaping, annotating and introducing it to today's readers. Each portion of commentary has been chosen for its salient insight, its rhetorical power and its faithful representation of the consensual exegesis of the early church." "The Ancient Christian Commentary on Scripture is a postcritical revival of the early commentary tradition known as the glossa ordinaria, a text artfully elaborated with ancient and authoritative reflections and insights. An uncommon companion for theological interpretation, spiritual reading, and wholesome teaching and preaching."--BOOK JACKET.
1. Genesis 1-11 -- 2. Genesis 12-50 -- 3. Exodus, Leviticus, Numbers, Deutoronomy -- 4. Joshua, Judges, Ruth, 1-2 Samuel -- 5. 1-2 Kings, 1-2 Chronicles, Ezra, Nehemiah, Esther -- 6. Job -- 7. Psalms 1-50 -- 8. Psalms 51-150 -- 9. Proverbs, Ecclesiastes, Song of Solomon -- 10. Isaiah 1-39 -- 11. Isaiah 40-66 -- 12. Jeremiah, Lamentations -- 13. Ezekiel, Daniel -- 14. The twelve prophets.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc -- History -- Early church, ca. 30-600 -- Sources; Bible. -- Commentaries; Bible. -- Criticism, interpretation, etc -- History -- Early church, ca. 30-600 -- Sources; Glossa ordinaria; Bible. -- Commentaries; Bible. -- Commentaries; Bible; Fathers of the church; Genesis (bijbelboek); Commentaries